2013
DOI: 10.1051/matecconf/20130504004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis by SEM, EBSD and X-ray diffraction of deformation textures of a copper wire drawn industrially

Abstract: Abstract. In this study, we tried to understand the texture evolution of deformation during the cold drawing of copper wire (99.26%) Drawn by the company ENICAB destined for electrical cabling and understand its link with the electrical conductivity. Characterisations performed show the appearance and texture development during the reduction of section of the wire. The texture is mainly composed of the fiber < 111 > / / DN (DN / / drawing axis) (majority) and the fiber < 001 > / / ND (minority) whose acuity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…This structure is fairly regular, which leads us to say that the crystallites are substantially isotropic, Figure 1a. And as prescribed by the literature [14][15]. Figure 1b shows the typical elongated aluminum grain structure noted in the artificially aged 6101 wires formed during prior deformation processes.…”
Section: Initial and Cold Drawn Statesupporting
confidence: 54%
“…This structure is fairly regular, which leads us to say that the crystallites are substantially isotropic, Figure 1a. And as prescribed by the literature [14][15]. Figure 1b shows the typical elongated aluminum grain structure noted in the artificially aged 6101 wires formed during prior deformation processes.…”
Section: Initial and Cold Drawn Statesupporting
confidence: 54%
“…DSC tests were carried out using a SETARAM (DSC131) differential scanning calorimeter. The samples for the DSC measurements weighted between 250 and 300 mg. Each sample was processed under Argon atmosphere, from 20 to 650°C, with four different heating rates (10,15,20 and 25°C/ min).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The elongated grains align parallel to the drawing direction. According to Fellah [12] and Baci et al [13], when the degree of deformation increases, the drawn wire acquires a textured microstructure so-called "wire-drawing of texture" [14,15]. Zidani et al [16] have also observed this kind of texture in the cold-drawn aluminum alloy (6101).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…al. [32], when the degree of deformation increases, the drawn wire acquires a textured microstructure so-called "wire-drawing of texture" [33,34]. This type of texture is usually encountered in the cold deformation of metallic materials and their alloys by "drawing"…”
Section: Light Microscopy Images Analysismentioning
confidence: 99%